The Growing Phenomenon of Private Tutoring - Dang, Hai-Anh (World Bank, 2012)
Does private tutoring increase parental choice and improve student achievement, or does it exacerbate social inequalities and impose heavy costs on households, possibly without improving student outcomes? Private tutoring is now a major component of the education sector in many developing countries, yet education policy too seldom acknowledges or makes use of it. This survey of the literature examines the extent of private tutoring, identifies the factors that explain its growth, and analyzes its cost-effectiveness in improving student academic performance. It also presents a framework for assessing the efficiency and equity effects of tutoring. The results suggest that even taking equity concerns into account, tutoring can raise the effectiveness of the education system under certain reasonable assumptions. Guidance is offered for attacking corruption and other problems that diminish the benefits of private tutoring.